DETERMINANT FACTORS ASSOCIATED WITH DIGITALIZATION OF LEADERSHIP COMMUNICATION AT HOSPITAL - Agustini, Ni Luh Putu Inca Buntari; Wardana, Dewa Gede Wisnu; Negara, I Gusti Ngurah Made Gusti Kusuma; Yusniawati, Yustina Ni Putu; Israfil, Israfil; Suyasa, I Gede Putu Darma (Nurse and Health: Jurnal Keperawatan, 2025)
Background: The digital era has accelerated the digitalization of organizational processes, including leadership communication. The emergence of digital leadership requires leaders to adapt their communication and leadership styles to dynamic, technology-mediated work environments. In hospital settings, effective digital leadership communication is essential to support coordination, decision-making, and quality nursing care. Purpose: This study aimed to identify determinants associated with the digitalization of leadership communication in hospitals. Methods: A cross-sectional study design was employed involving 131 nurses recruited through purposive sampling based on predefined inclusion criteria. Data were collected using structured questionnaires measuring leadership style, communication style, leadership skills, leader enthusiasm, and the implementation of digital leadership communication. Statistical analyses included the Spearman rho test, contingency coefficient, and multiple logistic regression to examine associations between variables. Results: The findings indicated that 94.7% of respondents perceived the implementation of digital leadership communication as good. Leadership style showed a moderate positive correlation with digital leadership communication (p = 0.000; r = 0.512). Communication style was not significantly associated with digital leadership communication (p = 0.434; r = 0.068). Leadership skills demonstrated a strong positive relationship (p = 0.000; r = 0.589), while leader enthusiasm showed the strongest association (p = 0.000; r = 0.698). Multivariate analysis confirmed that leadership skills and enthusiasm were the most influential determinants. Conclusion: Leader enthusiasm and leadership skills are key determinants of effective digitalization of leadership communication in hospital settings. Strengthening these competencies may enhance digital leadership practices and improve organizational communication in healthcare institutions.